Living alone, on my own : where’s the familial in their graying world? A study of seniors living alone in Singapore - Neo, Serene Wen Ying (2012)
This paper criticizes the Singapore state’s approach of invoking familial support as the first line of care in answering the challenges of an ageing population while the state comes in only to provide a framework to enable the family and community to play their part. Where then, in the larger schema of the policy framework on ageing, are seniors who have limited or no family support located? With specific reference to seniors who stay alone and have limited or no family support and are beneficiaries under Lions Befrienders Service Association (Singapore)’s Befriending Programme, I examine the problems created with certain assumptions that the state has institutionally reinforced with regards to the fundamental functions, practices and roles of the family. By contrast, I shall argue that a shift from the traditional, state-defined familism as a key pillar of support to a state-directed, community-based form of care, which encompasses a broader definition of the ‘family’, can more adequately deal with caregiving arrangements for vulnerable elders who are poor and socially isolated, either because they do not have any family or are estranged from them. As such, it may be appropriate to adopt new policy solutions, where primary caregiving for the elderly is not confined to who is considered kin but who is actually involved and providing it (Hirschfeld, & Wikler, 2003). As Singapore currently has no retirement communities, I put forth the above recommendation in establishing a proper and comprehensive service infrastructure to deal with aging and low-income elderly in a holistic and integrated manner.